RESULTS OF THE CORRELATION ANALYSIS - POLČIC, Ľudovít (Trends in education, 2009)
In this article the author analyses the relations among variables from the point of view of their coherence, in other words to what extent do the chosen techniques follow the different variables, phenomenons and to what extent they are related.
Keywords: correlation analysis; correlation coefficient; control group; experimental group.